Family and Community Medicine and Spirituality - Espino, Bruno Feitosa (Seven Editora, 2023)
Introduction: The association between Medically Unexplained Symptoms (MUS) and depressive and anxious conditions, named Common Mental Disorders (CMD) has been studied, but there are few studies in Brazil. Aims: To estimate prevalence of four MUS (irritable bowel, dyspepsia, chronic fatigue, and dizziness), its relationship with sociodemographic characteristics and co-occurrence with CMD. Method: The sample consists of 764 individuals, a subsample clinically evaluated by physicians, from the population survey ’São Paulo Megacity Mental Health Survey’. Psychiatric diagnoses were obtained through the SCID interview, according to DSM-IV. Information on the presence of MUS were obtained from validated scales in our country. Multivariable logistic regression model was used to study association of MUS and CMD. Results: Half of the sample presented at least one MUS, being more frequent in women, those aged between 35-49 years, ’low average’ income and among married people. Chronic fatigue was the most frequent symptom (30.4% in the total sample; 22.9% women; 7.5% men), followed by dyspepsia (26.8%; 19.3% in women and 7.5% in men), vertigo (19.6%; 15% in women and 4.5% in men), and irritable bowel (6%; 4.5% in women and 1.3% in men). There was an association between SEM and depression (RC 3.4; 95% CI, 2.4-4.8) and anxiety (RC 2.2; 95% CI, 1.5-3.0). The likelihood of these common mental disorders increased with increasing numbers of Mus. Conclusion: We confirm the association between MUS and CMD in this sample of the largest Brazilian city, indicating the need of a comprehensive approach in treatment. DOI: https://doi.org/10.56238/colleinternhealthscienv1-005